Analisis Strategi Emotional Branding dalam Upaya Membangun Loyalitas Konsumen Brand HMNS - Nurlaila Wa Rahma; Chalid Imran Musa; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Uhud Darmawan Natsir (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study examines HMNS, a local digital-native fragrance brand, in employing emotional branding to build consumer loyalty. Using a descriptive qualitative approach and SOR model, data from interviews with the brand’s founder and loyal consumers were analyzed. Results show that HMNS builds emotional bonds through storytelling, consistent visuals, and a relatable digital tone fostering trust and loyalty even before product trial. The findings affirm Gobe’s emotional branding theory and highlight the impact of narrative and personal values in driving long-term consumer attachment.